2020
DOI: 10.3389/frsc.2020.00034
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network for Driving Maneuver Identification Based on Inertial Measurement Unit (IMU) and Global Positioning System (GPS)

Abstract: Identification and translation of different driving maneuver are some of the key elements to analysis driving risky behavior. However, the major obstacles to maneuver identification are the wide variety of styles of driving maneuver which are performed during driving. The objective in this contribution through the paper is to automatic identification of driver maneuver e.g., driving in roundabouts, left and right turns, breaks, etc. based on Inertia Measurement Unit (IMU) and Global Positioning System (GPS). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For instance, some scholars used acceleration and angular velocity data collected through mobile phones and classified behaviors such as acceleration, deceleration, and turning [ 6 , 7 , 16 , 17 , 18 ]. Some scholars used in-vehicle devices embedded with IMU sensors to acquire vehicle motion data, applying machine learning methods for driving behavior monitoring [ 19 , 20 , 21 , 22 , 23 , 24 ]. Bonfati et al fused the CAN bus information of a vehicle and IMU sensor information to detect the driving behavior of the vehicle [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some scholars used acceleration and angular velocity data collected through mobile phones and classified behaviors such as acceleration, deceleration, and turning [ 6 , 7 , 16 , 17 , 18 ]. Some scholars used in-vehicle devices embedded with IMU sensors to acquire vehicle motion data, applying machine learning methods for driving behavior monitoring [ 19 , 20 , 21 , 22 , 23 , 24 ]. Bonfati et al fused the CAN bus information of a vehicle and IMU sensor information to detect the driving behavior of the vehicle [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars applied a dynamic time warping (DTW) algorithm to detect and identify driving behaviors [ 16 , 17 , 39 ]. Other scholars applied convolutional neural networks (CNN) with multiple sources of fused data for identifying car maneuvers, and comparisons with other models such as a HMM, RF, artificial neural network (ANN), KNN, and SVM were made [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Junior et al used four algorithms, including multilayer perceptron (MLP), SVM, RF and Bayesian network, to identify driving behaviors such as fast lane changes, turns, braking, and acceleration, and the results showed that RF and MLP demonstrated better performances [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The multilevel models of driving style assessment described in [12] take into account behavioral aspects (driver's emotions and driver's condition) to ensure greater safety and comfort. Machine learning methods for driving style classification are reflected in the works [13]- [20]. The work [13] shows the expediency of using the support vector machine to identify the driving style.…”
Section: Introductionmentioning
confidence: 99%
“…CNN, long short-term memory (LSTM) network, and pre train-LSTM [15], [17], [20], random forest [16] - [14], [17], [20]/+ [15], [16] -+ + Application of self-organizing maps [21] + + Classification method, which is enabled by ensemble learning [23] --+ +…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning approaches have been demonstrated to have an excellent predictive power in recognizing patterns in data (Paolanti and Frontoni, 2020). Among a wide range of algorithms, convoluted neural networks (CNNs), support vector machine (SVM), and random forest (RF) are popular approaches used to identify underlying associations in images (AgajanianOluyemiVerkhivker, 2019;Ahmed, 2020). These techniques are increasingly being introduced in material science to identify concealed property relationships (Bulgarevich et al, 2018;Himanen et al, 2019;Xia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%